Tough, strong, and biodegradable composite film with excellent UV barrier performance comprising soy protein isolate, hyperbranched polyester, and cardanol derivative. Issue 13 (12th June 2019) - Gu, Weidong; Liu, Xiaorong; Li, Feng; Shi, Sheldon Q.; Xia, Changlei; Zhou, Wenrui; Zhang, Derong; Gong, Shanshan; Li, Jianzhang
Abstract : Tough and biodegradable soy protein isolate film with excellent UV barrier performance by hyperbranched polyester, and cardanol derivative. Abstract : The preparation of strong, tough, and biodegradable soy protein isolate (SPI)-based composite films remains challenging. The simulation of natural structures is highly desirable in the manufacture of synthetic polymer materials because it may significantly improve their mechanical properties and extend their applicability. Herein, we report a facile strategy for preparing a biodegradable SPI-based composite film by incorporating a biomass-derived, water-soluble hyperbranched polyester (HBPE) and a polyfunctional cardanol derivative. The fabricated SPI-based composite film has high tensile strength (11.6 MPa) and an excellent breaking strain (123%). This outstanding performance may be attributed to: the fractional free volume increase arising from the introduction of nanosized cavities into the matrix; the strain-induced orientation crystallization of the SPI-based composite film following incorporation of the polyfunctional cardanol derivative; and the strong intermolecular sacrificial hydrogen bonds and stable covalent bonds confined within the matrix. Furthermore, the biodegradable SPI-based composite film has excellent UV-barrier performance owing to the inclusion of the cardanol derivative.